PEDAGOGICAL OPPORTUNITIES FOR EDUCATION OF STUDENTS THROUGH SPORTS COMPETITIONS - Inomov Fakhriddin Ormonovich (Galaxy International Interdisciplinary Research Journal, 2024)
The article covers the issues of regular sports activities of secondary school students and participation in sports competitions. It has also been written about the positive impact of sports competitions on the all-round learning of students.